(untitled) (Faculty of Education Scientific Journal, 2024)
The current research aims to identify the manifestations of emotional divorce among a sample of married women in the city of Al-Khums. The research sample included (160) married women. The emotional divorce scale was prepared by the researcher, and this scale was valid and reliable. Several statistical methods were used to achieve the objectives of the research, such as: Pearson’s correlation coefficient, Kornbach’s alpha, weighted mean, and one-sample t-test. The researcher found a positive statistically significant relationship at the level (0.01) between emotional divorce and its three dimensions: weak emotional attachment, loss of love and affection, and poor sexual satisfaction. The results of the research revealed that the level of emotional divorce among the respondents is below average, and it turned out that the most manifestations of emotional divorce were: fear of the unknown, rarely going out with the husband for a walk, constant preoccupation with work, mutual blame between the spouses, scarcity of physical contact with the husband, scarcity of exchanging gifts with the husband, lack of expression of joy with fun and laughter, and scarcity of exchange kind words with the husband, lack of sexual activity and lack of sexual satisfaction, and finally several recommendations and proposals were introduced in the light of the research results.